2014
DOI: 10.1369/0022155414558063
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia Does Not Alter Vascular Growth and Expression of CD31 and Vascular Endothelial Cadherin in Human Placentas

Abstract: SummaryPreeclampsia is characterized by maternal endothelial dysfunction (e.g., increased maternal vascular permeability caused by the disassembly of endothelial junction proteins). However, it is unclear if preeclampsia is associated with impaired vascular growth and expression of endothelial junction proteins in human placentas. Herein, we examined vascular growth in placentas from women with normal term (NT) and preeclamptic (PE) pregnancies using two endothelial junction proteins as endothelial markers: CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Despite the significant overexpression of endoglin (CD105) that is expected to be correlated with angiogenesis, in the present study we found MVD in PE to be comparable to control group. Similarly were the results reported by Li et al, (2015) [30] .…”
Section: Similar To Our Results Sankar Et Al (2012) Andsupporting
confidence: 89%
“…Despite the significant overexpression of endoglin (CD105) that is expected to be correlated with angiogenesis, in the present study we found MVD in PE to be comparable to control group. Similarly were the results reported by Li et al, (2015) [30] .…”
Section: Similar To Our Results Sankar Et Al (2012) Andsupporting
confidence: 89%
“…In an arterial pathology such as preeclampsia, CD31 immunoreactivity is lower in the placenta than in control pregnancies [24,26]. However, Li et al [27] showed no significant differences in CD31 level in the placenta of women with preeclampsia. In general, angiogenesis and lymphangiogenesis are modified in vascular pathology [28].…”
Section: Discussionmentioning
confidence: 96%
“…[12,14,22,25] A single dose of ITE (20 ”M) rapidly decreased ( p < 0.05) AhR protein levels in HPAEC by 55.9, 72.2, 70.6, 74.6, and 59.8% on 1, 8, 16, 24, and 48 hr, respectively (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Immunolocalization of AhR was visualized by indirect detection via the avidin: biotinylated-peroxidase complex method (Vector Laboratories, Burlingame, CA) as described. [23–25] Briefly, after deparaffinized and dehydrated, the microarray was boiled in a 10 mM citrate buffer solution (pH 6.0) in a microwave for 10 min for antigen retrieval. Endogenous peroxidase activity was quenched using 3% H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%